Persistence of Labor Market Disparities in Indonesia: An Analysis of Regional Productivity and Wage Gaps, 2018–2023: Persistensi Disparitas Pasar Tenaga Kerja di Indonesia: Analisis Kesenjangan Produktivitas dan Upah Regional 2018–2023 - Erin Rismaya; Ayus Ahmad Yusuf (jsd: Journal of Society and Development, 2026)
Amid Indonesia's ambition to escape the middle-income trap, the anomaly between productivity growth and wage welfare at the regional level has become a critical structural barrier requiring profound attention. This disparity is not merely a statistical issue but a socio-economic reality that determines the future stability and resilience of the national economy. This study aims to analyze the persistence of labor market disparities in Indonesia, focusing on the dynamics of regional productivity and wages during the 2018–2023 period. Adopting a quantitative descriptive-comparative approach using secondary data from the Central Bureau of Statistics across 34 provinces, this research examines the elasticity of wages relative to productivity in leading sectors. The results indicate persistent inequalities between Java and non-Java regions, where regional wage growth often lags behind productivity surges, particularly during the post-pandemic economic recovery phase. This phenomenon suggests that the wage-productivity transmission mechanism is still hindered by wage policies that are not yet fully adaptive to local performance realities and agglomeration advantages. Theoretically, this research contributes to the labor economics literature by modeling the wage-productivity interaction within the economic transformation of a developing nation. Practically, this study formulates strategic recommendations for policymakers to design performance-based regional wage systems to narrow inter-regional economic gaps and create a more inclusive labor market across Indonesia.